Fundamentals of Ensuring the Financial Stability of the Country’s Banking System - Gayratovich, Sadykov Iskandar (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2024)
This article discusses various approaches to ensuring the financial stability of the country’s banking system in any conditions of its viability, carrying out all banking operations in accordance with customer requirements and ensuring the financial stability of banks, which are the implementation of differentiation of financial stability depending on goals and objectives. Also, to date, improving the financial stability of commercial banks consists in determining the structure of assets and liabilities of banks, increasing the level of profitability of banks, stimulating the need for effective management of existing banking risks. On the way to achieving these goals, the author conducted research and obtained results.